Ab initio calculations on electronic, optical, and thermoelectric properties of (Si, Pb) (co)-doped ZnS for solar cell device applications. (September 2019) - Absike, H.; Labrim, H.; Hartiti, B.; Douhou, K.; Ez-Zahraouy, H.
Abstract: In the present work, the electronic structure, optical and thermoelectric properties of (SiPb) doped and co-doped ZnS compounds with different concentrations (x = 3.125%, 6.25% and 12.5%) are investigated using the ab initio full-potential linearized augmented plane wave (FP-LAPW) method. This study has been done by applying the generalized gradient approximation and the modified Becke-Johnson (mBJ) exchange potential. The obtained results show that the lattice parameters can be modified with doped atoms impurity. The optical band gap decreases with the increasing of Si and Pb doping concentration and found to be 1.41 eV, 1.38 eV and 1.04 eV for 6.25% of Si and Pb doping and co-doped respectively. Consequently, the dielectric functions, absorption coefficient, optical conductivity for doped and co-doped ZnS are predicted. The present result is in a good agreement with the available experimental one dealing with the undoped ZnS. Thus, we showed that the absorption coefficient increases with increasing SiPb doping and co-doping concentration compared to the undoped ZnS compound. The evolution of the Seebeck coefficient and electrical conductivity at different temperature and doping levels are investigated and the result shows that at room temperature, 12.5% of Si-doped ZnS, reaches the maximum values. The original Zn1-x Six S brings a promising physical property which can be used for optoelectronic and thermoelectric device applications. Highlights: Electronic, Optical and Thermoelectric properties of Pb, Si doped and co-doped ZnS. Properties of band structure, absorption coefficient, electrical conductivity and optical conductivity are investigated. Density functional theory are performed using mBJ method.